THE ECONOMIC IMPACT OF COMMUNITY ENTREPRENEURSHIP ON WOMEN'S EMPOWERMENT: A CASE STUDY OF RUMAHKU BOYOLALI - Dwi Prasetyani; Hilmah Zuryani (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2026)
The aim of this research is to explore narratives of the experiences of women involved in community-based entrepreneurial empowerment in Rumahku Boyolali in 2024, analyze the impact of empowerment on the development of their businesses, analyze the challenges and opportunities they face in running businesses and interacting with the entrepreneurial community. The method used is a qualitative approach, while the research technique uses orange mosaic geo-maps analysis, Sara Longwe model gender analysis, and SWOT analysis. The results of the research show that the Rumahku Boyolali community-based entrepreneurial empowerment has had a positive impact on women in running their businesses. The government is required to step in to assist in the development of community-based entrepreneurial empowerment at Rumahku Boyolali